Availability and use of PET in patients with brain tumours: a European Organisation for Research and Treatment of Cancer - Brain Tumour Group (EORTC-BTG) survey - Mair, Maximilian; Lohmann, Philipp; Galldiks, Norbert; Belting, Mattias; Brandal, Petter; Broen, Martinus P. G.; Cicone, Francesco; Daisne, Jean-François; Ducray, François; Ehret, Felix; Furtner, Julia; Jakola, Asgeir S.; et al. (European journal of nuclear medicine and molecular imaging, 2025)
Positron emission tomography (PET) is increasingly used in neuro-oncology. However, little is known about its application across European institutions and reasons for variable implementation.
Gesehen am 05.11.2025